Rare Case : Lymphangioleiomyomatosis in a 28 year-old woman with spontaneous bilateral pneumothorax - Matabei, Shannon Conversia Pdabo; Djajalaksana, Susanthy; Chozin, Iin; Erawati, Dini; Wardhana, Koernia; Yudhanto, Hendy; Rahman, Perdana; Chen, Chung-Yu (Malang Respiratory Journal, 2025)
Introduction: Lymphangioleiomyomatosis (LAM) is an extremely rare disease with no known exact cause, in which there are abnormalities in the development of smooth muscle cells. This condition manifests in multiple organs, one of which is the lungs. Prevalence of LAM is 1 in 1,000,000, most commonly found in women of reproductive age. Pneumothorax occurs in two-thirds of LAM patients. It is possibly underdiagnosed in Indonesia. Case report: A 28-year-old woman came to the Emergency Department with sudden severe shortness of breath. Chest X-ray shows bilateral pneumothorax predominantly on the left side, and a chest tube was installed. Thorax MSCT revealed multiple cysts in all areas of lungs, while abdominal USG and MRI discovered masses in uterus and right adrenal. Left bullectomy-thoracotomy and lung biopsy were performed, with histopathology result supporting LAM. The patient was stable post surgery. LAM is associated with mutations in TSC1 or TSC2 genes, resulting in cystic changes caused by LAM cells proliferation in the lungs. In this patient, bilateral pneumothorax resulted from multiple subpleural cysts which eventually ruptured. Diagnosis of LAM was established by radiological imaging and lung biopsy. Surgical and non-surgical interventions were performed to address the acute manifestations of LAM. Unfortunately, Sirolimus which is the recommended long-term medication for LAM is not yet available in Indonesia. Conclusion: LAM is a rare disease. It’s important for clinicians to be familiar with this condition, aware of its progression and possible recurrence of pneumothorax, in order to provide appropriate interventions.